Case Report: COVID-19 Infection With Gastrointestinal Symptoms and Mood Disorder: Criticalities in Differential Diagnosis, Therapy and Management of Complications - Borriello, Giuseppina; Lavatelli, Lisa; Ruzzi, Francesca; Panariello, Adelaide; Percudani, Mauro Emilio (Frontiers in Psychiatry, 2021)
During this pandemic Italy was deeply hit by the burden of the COVID-19. Current studies reveal that respiratory symptoms of COVID-19 represent the most common manifestations at presentation. The incidence of less common gastrointestinal symptoms varies significantly among different study populations. Liver injury is also described at different degree. We describe the case of a 20-year-old woman confirmed as Sars-CoV-2 positive by nasopharyngeal swab-PCR test, admitted to the COVID-only- Psychiatric Ward, set up in Niguarda Hospital in Milan on March 2020, for a depressive episode characterized by depressed mood and anorexia. In comorbidity we report a previous avoidant/restrictive food intake disorder present since childhood and a Border Personality Disorder according to the DSM V. On the admission to the ward we administered the Hamilton Depression Rating Scale with a total score of 29 suggesting severe depression. During the hospitalization she developed a clinical picture with increasing vomiting and diarrhea, nausea, abdominal pain along with fever and no respiratory symptoms. She also showed abnormalities in liver function indices. At the same time she showed clinophilia and persistent food avoidance that, initially, led to attribute all the symptoms to her psychiatric disorders. We prescribed the already ongoing therapy with lithium carbonate and SSRI. On the second day of hospitalization, along with the worsening of the gastrointestinal symptoms, we started therapy with hydroxychloroquine with a no significant remission of nausea and vomiting but with a further increase in liver function indices suggesting liver damage. This led us to suspend the treatment with hydroxychloroquine for the suspect of a drug induced injury. The depressive symptoms improved rapidly as opposed to the patient’s overall condition. The gastrointestinal symptoms resolved with the evidence of the recovery from infection. In this report we underline the importance of investigating the physical symptoms in a patient with a history of mental disorder especially during an undergoing pandemic. During this pandemic, specialists from various fields were called upon to support teams working with COVID patients and to acquire new skills out of necessity, fostering a multidisciplinary approach and cooperation. Acknowledgements We thank Dr. Martina Sommariva, Language Specialist, for the support